Kepastian Hukum dan Efektivitas Pembuktian Digital dalam Penyidikan Online Fraud: Analisis Normatif Pasal 235 KUHAP Baru dan Implementasinya di Polres Cimahi - Yudhi Hariyanto; Haidan Angga Kusumah (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
The surge in online fraud in Indonesia demands reliable digital evidence procedures, yet the normative frameworks of the Electronic Information and Transactions (EIT) Law and the new Criminal Procedure Code (Law No. 20/2025) lack adequate technical guidance for investigators at the regional level. To analyze the adequacy of digital evidentiary norms and their implementation in online fraud investigations at the Cimahi Regional Police. This normative juridical study employs statutory, conceptual, and case approaches. Primary data were obtained through limited structured interviews with investigators of the Criminal Investigation Unit of the Cimahi Police, supplemented by document study of legislation, court decisions, and legal literature. Qualitative-prescriptive analysis was conducted using legal certainty theory and law enforcement effectiveness theory. Three layers of normative gaps were identified: a procedural void in evidence acquisition and authentication (leemten), vague authenticity parameters in Article 235(3) (vage normen), and disharmony between the broad authority of Article 43 of the EIT Law and the absence of police technical guidelines. At the implementation level, investigators face limited forensic competence, facilities, and laboratory access. Technical implementing regulations, digital forensic SOPs, investigator certification, and early coordination with prosecutors are urgently needed to bridge the gap between normative standards and operational capacity. This is the first study to integrate a normative analysis of Article 235 of the new Criminal Procedure Code (effective January 2, 2026) with a limited empirical evaluation of online fraud investigation practices at the police-precinct level, offering an integrated evaluation framework linking legal certainty with law enforcement effectiveness in digital evidence.